Tinjauan Hukum Islam Terhadap Operasi Selaput Dara Wanita: Islamic Law Review on Women's Hyper Operation - Nur Aflaha Hasan; Rosmita, Rosmita (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This article aims to find out the views of Islamic law on a woman's hymen surgery. The research methodology used is library research which relies on a critical and in-depth study of research materials and results related to the topic of the study problem, using a juridical and sociological approach. The results of the research obtained are that contemporary scholars give different opinions. Some absolutely forbid whatever the reason and some allow it under certain conditions. The differences of opinion of the scholars on the issue of hymen surgery can be concluded as follows: a) If the hymen is only ruptured due to sexual intercourse in marriage or adultery which is known to many people, the scholars agree to forbid it. b) If the rupture of the hymen is due to adultery which is unknown to others, rape or other than sexual intercourse, this is where the scholars differ, some allow it on condition that the operation must be performed by a female doctor.